In-vitro antioxidant and anti-inflamatory activities of Pituranthos chloranthus and Artemisia vulgaris from Tunisia - Ben Nasr, Soumeya (2020)
Pituranthos chloranthus and Artemisia vulgaris L. are two of the most important aromatic and medicinal species from the Apiaceae and Asteraceae families, respectively. They are traditionally used in certain pathologies in which inflammatory processes are involved. The present study investigates the potential of aqueous extracts of Tunisian P. chloranthus and A. vulgaris as a natural alternative source of antioxidant and anti-inflammatory activities using in-vitro techniques. The antioxidant activities of aqueous extracts were evaluated through several assays: capacity for scavenging free radicals (ABTS, DPPH, hydroxyl, superoxide, nitric oxide); and total antioxidant capacity by ferric reducing power activity and inhibition of lipid peroxidation by thiobarbituric acid reactive species (TBARS) method. The anti-inflammatory activity was evaluated through the lipoxygenase (LOX) inhibitory activity. P. chloranthos aqueous extract presented higher concentration of total phenols than A. vulgaris extract, nevertheless higher capacity for scavenging ABTS, superoxide, hydroxyl. and NO free radicals. In the presence of liver homogenate, both extracts had poorer antioxidant activity than in the remaining lipid substrates. P. chloranthos extract had a higher ability for inhibiting lipoxygenase twice higher than A. vulgaris, while it had lower capacity for reducing Fe3+ than P. chloranthos extract. Our results suggest that there are differences of antioxidant activity between both samples, but also the strength for inhibiting the oxidation is highly dependent on the method used.